A model for the minimum mass of bound stellar clusters and its dependence on the galactic environment - Trujillo-Gomez, Sebastian; Reina-Campos, Marta; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present a simple physical model for the minimum mass of bound stellar clusters as a function of the galactic environment. The model evaluates whic